Velocity field and dynamics behavior of a boiling droplet during impact onto a molten phase change material - Mohammadreza Asadi; Mohammad Behshad Shafii; Amirreza Ghahremani (International Journal of Thermofluids)
Droplet impact is a widely used method for creating direct heat transfer between two fluids. This method enhances heat transfer between the working fluid and the phase change material (PCM). Therefore, a thorough investigation is carried out on the impact of an acetone droplet on a molten paraffin's pool surface, which leads to the simultaneous boiling of the acetone droplet and solidifying part of the paraffin in contact with the acetone, thereby significantly accelerating the slow phase change rate of the PCM used in thermal energy storage (TES) systems across various industries. The dynamics of impact and crater's evolution have been reported with varying Weber numbers (74–375), and temperature of the molten PCM's pool surface (65–90 °C). Furthermore, the experimental data obtained for the crater depth is compared with theoretical equations. Six regimes have been observed by changing the Weber number and pool surface temperature. An increase in the Weber number or surface temperature leads to a larger crater and higher jet and crown. As a novelty, to gain a more physical insight into this intricate phenomenon, the velocity field resulting from the impact, perpendicular and parallel to the pool surface, is obtained using the particle image velocimetry (PIV) and high-speed imaging for the first time. Upon impact, maximum velocity is at the lowest point of the crater, equaling approximately 10 % of the impact velocity. Also, solidified paraffin area increases with an increase in the Weber number (up to We = 297) and a decrease in the surface temperature. Solidified area at this Weber number at T = 90 °C is 9.3 % of that at 65 °C. Finally, the acetone vapor is visualized using Z-type Schlieren imaging. Acetone evaporation rate is increased with Weber number increment.